Climate Change Predicted to Negatively Influence Surface Soil Organic Matter of Dryland Cropping Systems in the Inland Pacific Northwest, USA - Morrow, Jason G.; Huggins, David R.; Reganold, John P. (Frontiers in Ecology and Evolution, 2017)
Soil organic matter (SOM) is a key indicator of agricultural productivity and overall soil health. Currently, dryland cropping systems of the inland Pacific Northwest (iPNW) span a large gradient in mean annual temperature (MAT) and precipitation (MAP). These climatic drivers are major determinants of surface SOM dynamics and storage characteristics. Future climate change projections through 2070 indicate significant shifts in MAT and MAP for the iPNW. We assessed surface (0–10 cm) soil organic C and N as well as active and recalcitrant fractions of SOM within long-term experiments representing different tillage regimes and cropping intensities across the current climatic gradient of the iPNW. We discovered that current levels of soil C and N as well as various SOM fractions were positively correlated with MAP and negatively correlated with MAT. Furthermore, these climatic drivers were more influential than either tillage regime or cropping intensity in determining SOM levels and characteristics. Soil organic C and total N as well as the hydrolyzable and non-hydrolyzable fractions were negatively correlated with the current ratio of MAT to MAP, called the climate ratio. Future climate projections (2030 and 2070) forecast an increase of the climate ratio, thus predicting declines in surface SOM and associated soil health across the iPNW.